Synthesis and Photophysical Properties of Alkoxysilyl Derivatives of Dibenzoylmethanatoboron Difluoride - Kononevich, Yuriy N.; Meshkov, Ivan B.; Voronina, Natalia V.; Surin, Nikolay M.; Sazhnikov, Viacheslav A.; Safonov, Andrei A.; Bagaturyants, Alexander A.; Alfimov, Mikhail V.; Muzafarov, Aziz M. (Heteroatom chemistry, 2013)
ABSTRACT Alkoxysilyl derivatives of dibenzoylmethanatoboron difluoride (DBMBF2) are synthesized by the hydrosilylation reaction of the corresponding O‐allyl derivatives of DBMBF2 with triethoxysilane. The photophysical properties of the synthesized O‐allyl and alkoxysilyl derivatives are investigated. It is found that the absorption and fluorescence spectra of the DBMBF2 derivatives essentially depend on the position of the O‐allyl or O‐propyl alkoxysilyl substituent. The highest fluorescence quantum yield is obtained for the para‐position, whereas the substitution at the meta‐position gives the largest bathochromic shift in the fluorescence spectrum. Density functional theory calculations of the structures and time‐dependent density functional theory calculations of the gas‐phase excitation and emission energies of alkoxysilyl derivatives are performed at the PBE0/SVP level of theory. Some spectral features of para‐, ortho‐, and meta‐substituted derivatives can be adequately explained by the overlapping of two absorption bands.